Pemidanaan Terhadap Anak Sebagai Pelaku Dan Korban Dalam Tindak Pidana Pencabulan (Analisis Terhadap Putusan Hakim Nomor 8/Pid.Sus.Anak/2016/PN.Trt dan Nomor 9/Pid.Sus.Anak/2016/PN.Trt) - Denny Reynold Octavianus; mahmud mulyadi; Marlina Marlina; Edy Ikhsan (Iuris Studia: Jurnal Kajian Hukum, 2021)
The application of punishment to minors as perpetrators of criminal acts of obscenity in the judge's decision does not provide a sense of justice for minors and their families as victims of obscenity. This study discusses the sentencing of minors as perpetrators of criminal acts of obscenity in cases of obscenity against child victims who are both underage in Decision Number 8/Pid.Sus.Anak/2016/PN.Trt and Decision Number 9/Pid .Sus.Anak/2016/PN.Trt dated September 6, 2016. It was concluded that the imposition of punishment on child perpetrators for the obscenity case in the Tarutung District Court Decision did not fulfill the sense of justice in a balanced manner according to the principle of proportional equality (distributive justice). Considerations for treatment and rehabilitation, as well as utility are not balanced, only for child actors. Child perpetrators are subject to maatregel, but child victims are not recovered from their trauma. Fines, compensation of any kind are not imposed on child perpetrators or their families for the costs of recovery, treatment, rehabilitation of child victims. Alternative legal sanctions for the parents of the perpetrator's child should be subject to civil liability for compensation. In order to have a deterrent effect and special prevention for parents, be careful, alert and control their children from criminal acts, continuous supervision, provide them with formal and non-formal education, and so on. The right to compensation should also be handed down by the court judge to the perpetrator even though it was not requested in the public prosecutor's indictment